La tierra “esclava” del Ática en el s. VII a.C.: campesinos endeudados y hectémoros - Valdés Guía, Miriam (Gerión. Revista de Historia Antigua, 2006)
The situation of the hektemoroi and of the Attic land is one of the most disputed subjects of Athenian history before Solon. In this article we propose the existence of a variety of situations concerning the peasants and the land. Anyway, the clue for understanding the historical processes of that moment, is the acknowledgement of, essentially, two situations concerning the Attic peasants (in correspondence with the later zeugitai and thetes): in one hand, the existence of middle/little proprietors of a kleros which are in a process of degradation and loose of land; in the other hand, the existence of hektemoroi/ thetes, not proprietors of the kleros that they worked, tenants or poor lessees who live in continual tension and precarious conditions, in strong dependence circumstances. Besides, both groups are liable, literally, of being sold as slaves.